2012
DOI: 10.1177/0954405412461864
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding parameters optimization of heterogeneous tailored welded blank sheets of aluminium alloys 6061 and 5083 using response surface methodology

Abstract: Today, tailored welded blank sheets have found various applications in automotive, aeronautic and many other industrial fields. One of the most efficient methods for production of tailored welded blank sheets is application of the friction stir welding process. In the present article, the effect of friction stir welding parameters on the microstructure and mechanical properties of heterogeneous tailored welded blank sheets made from aluminium alloys of types 5083-H12 and 6061-T6 with the similar thickness of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…23 Also, the nondissolved precipitates will get coarser due to an extra heat input. 24 The predicted and measured tensile strengths of the dissimilar joints produced by the FSW and the TIG techniques are summarized in Table 8. According to this table, there is a good agreement between the predicted and measured tensile strengths, indicating the capability of RSM in modeling and predicting results of the processes.…”
Section: Resultsmentioning
confidence: 99%
“…23 Also, the nondissolved precipitates will get coarser due to an extra heat input. 24 The predicted and measured tensile strengths of the dissimilar joints produced by the FSW and the TIG techniques are summarized in Table 8. According to this table, there is a good agreement between the predicted and measured tensile strengths, indicating the capability of RSM in modeling and predicting results of the processes.…”
Section: Resultsmentioning
confidence: 99%
“…Data variance analysis showed that the rotational speed and diameter of a tool are the major and the minor significant factors, respectively. Similarly, this is seen in studying the effect of welding factors on the microstructure and mechanical strength of heterogeneous tailored welded blank sheets (5083-H12 and 6061-T6 Al alloys) [18]. Optimization of FSW parameters was established in different conditions of base material and the microstructures of the welded condition compared with the postweld heat-treated microstructures welded in annealed and T6 condition [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on their results, underwater welding of AA5083 alloy produced good tensile properties, and also significant reduction in void fraction was observed in the weld zone. FSW tailor welding process of Al6061-Al5083 blank sheets was optimized by Ghaffarpour et al 2 using response surface methodology. Nguyen et al 3 predicted failure loads of friction stir spot welding joint of Al6061-T6 sheets using finite element analyses.…”
Section: Introductionmentioning
confidence: 99%